2010
DOI: 10.1364/oe.18.010650
|View full text |Cite
|
Sign up to set email alerts
|

Second-order statistics of stochastic electromagnetic beams propagating through non-Kolmogorov turbulence

Abstract: We present a detailed investigation, qualitative and quantitative, on how the atmospheric turbulence with a non-Kolmogorov power spectrum affects the major statistics of stochastic electromagnetic beams, such as the spectral composition and the states of coherence and polarization. We suggest a detailed survey on how these properties evolve on propagation of beams generated by electromagnetic Gaussian Schell-model sources, depending on the fractal constant alpha of the atmospheric power spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…Including both the inner-and outer-scale effects, the non-Kolmogorov spectrum is defined as [35][36][37][38][39][40][41] …”
Section: Analysis Of Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Including both the inner-and outer-scale effects, the non-Kolmogorov spectrum is defined as [35][36][37][38][39][40][41] …”
Section: Analysis Of Theorymentioning
confidence: 99%
“…Then a non-Kolmogorov model is presented [33], which is more general to describe the practical atmosphere and reduces to the Kolmogorov model in the case of the generalized exponent α = 11/3. It has been reported that, based on this non-Kolmogorov spectrum, optical wave will provide a different property when propagating in non-Kolmogorov turbulence [35][36][37][38][39][40][41]. Moreover, due to the high elevation angle propagation and the altitude of the relay system, the relay propagation will inevitably propagate in non-Kolmogorov turbulence, and it requires studying the relay propagation in non-Kolmogorov turbulence for more accurate results for practical applications of relay propagation, i.e., free-space communication.…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric propagation of laser beams is important for remote sensing, tracking, and longdistance optical communications, as well as military applications; an extensive study of laser-beam propagation through atmospheric turbulence has been made [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Laser beams have been extended from fully coherent to partially coherent beams [1][2][3][4], from monochromatic to polychromatic beams [5][6][7], from scalar beams to vector beams [8,9], and from a single beam to array beams [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The parameter "α" is the power-law for the spectrum of the index of refraction fluctuations, and the generalized power spectrum reduces to the conventional Kolmogorov spectrum when the exponent value α = 11/3 [5,6]. Based on this model, average spreading of a Gaussian beam array, spreading and direction of Gaussian-Schell model beam and secondorder statistics of stochastic electromagnetic beams in non-Kolmogorov turbulence have been studied [3,7,8]. However, to our knowledge, the propagation of other types of beams in non-Kolmogorov turbulence have rarely been taken into account, even though the propagation properties of various types of laser beams in Kolmogorov turbulence have been widely studied [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%